Predicting the maturity and organic richness using artificial neural networks (ANNs): A case study of Montney Formation, NE British Columbia, Canada - Barham A.; Ismail M.S.; Hermana M.; Padmanabhan E.; Baashar Y.; Sabir O. (Elsevier B.V., 2023)
Backpropagation; Feedforward neural networks; Forecasting; Organic carbon; Petroleum reservoirs; Petrophysics; Statistical tests; Tight gas; Well testing; British Columbia , Canada; Feedforward neural networks (FFNN); Geochemical datasets; Mathematical relationship; Petrophysical properties; Regularization technique; Tight gas reservoirs; Total Organic Carbon; Oil well logging